Impact of Orthodontic Treatment on Periodontal Tissues: A Narrative Review of Multidisciplinary Literature - Angelina Gorbunkova; Giorgio Pagni; Anna Brizhak; Giampietro Farronato; Giulio Rasperini (International Journal of Dentistry)
The aim of this review is to describe the most commonly observed changes in periodontium caused by orthodontic treatment in order to facilitate specialists’ collaboration and communication. An electronic database search was carried out using PubMed abstract and citation database and bibliographic material was then used in order to find other appropriate sources. Soft and hard periodontal tissues changes during orthodontic treatment and maintenance of the patients are discussed in order to provide an exhaustive picture of the possible interactions between these two interwoven disciplines.